The foreign direct investment and economic growth in Malaysia: an OLS approach / Tismazammi Mustafa and Asma' Rashidah Idris - Mustafa, Tismazammi; Idris, Asma' Rashidah (2021)
Recently, Malaysia has sustained FDI inflows and outflow position and emerged as the fifth largest investor among the developing economies in the Asia region (UNTACD, 2005). This study analyses the effect of Foreign Direct Investment (FDI) on economic growth in Malaysia. The Ordinary least Square (OLS) method is used to investigate the relationship between FDI and economic growth. The controlled variables are inflation and export. This paper is conducted using annual data in Malaysia over the 1989 till 2018 periods and used annual data from IMF International Financial Statistics tables, published by the International Monetary Fund. The OLS suggested that FDI has a direct positive effect on GDP. On the other hand, others control variables, inflation and exports, have different signs of impact on GDP.